Análise de uma biblioteca de mutantes de Xanthomonas citri subsp. citri quanto à patogenicidade - Silva, Ana Carolina Buzinari da [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The study of plant-pathogen interaction is very important to citrus canker understanding, justifying the search for virulence and pathogenicity related genes in Xanthomonas citri subsp. citri (Xac), causal agent of this disease. In this study, a random mutagenesis by Tn5 transposon insertion into Xac’s genome was performed. Eight thousand mutants were produced and 292 mutants were tested in planta. From those, five mutants expressed altered symptomatology, two showed complete absence of symptoms and three reduced hyperplasia. Gene sequences analysis where transposon was inserted, indicated mutations in purF, yapH and oar genes, in a region that codes for a hypothetical protein (XAC0196), and in a region between pobB (XAC0362) and glpR (XAC0361) genes. Analysis of bacteria growth curve in planta showed that, except for purF gene, all the others genes may be involved in Xac pathogenicity. Two of these genes, yapH and oar, are described as bacterial adhesion related genes, highlighting that interference in this process has direct influence in the Xac infection success. The importance of hypothetical protein identification is emphasized, since it presented attenuated symptomatology when mutated

O estudo da interação planta-patógeno é de grande importância para o entendimento do cancro cítrico, justificando assim a busca por genes que estejam ligados a patogenicidade e virulência em Xanthomonas citri subsp. citri (Xac), agente causal dessa doença. Neste estudo, foi realizada mutagênese aleatória por inserção do transposon EZ-Tn5 in vitro no genoma da Xac. Obteve-se 8000 mutantes onde 292 foram conduzidos em ensaio experimental in planta. Cinco mutantes expressaram sintomatologia alterada, dois com ausência total de sintomas e três com leve hiperplasia. A análise da sequência dos genes onde se inseriu o transposon indicam mutações nos genes purF, yapH, oar, um gene que codifica uma proteína hipotética (XAC 0196), e na região entre os genes pobB (XAC0362) e glpR (XAC0361). As análises de curvas de crescimento bacteriano in planta demonstraram que, exceto o gene purF, todos os demais podem ser genes envolvidos na patogenicidade de Xac. Dois destes, yapH e oar são descritos como relacionados à adesividade bacteriana, evidenciando que a interferência nesse processo exerce influência direta no sucesso da infecção de Xac. Destaca-se também a importância da identificação de uma proteína hipotética, já que essa apresentou sintomatologia atenuada quando ocorreu a inserção do transposon
Keywords: Cancro citrico; Mutagenese; Patogenicidade; Genes; Xanthomonas; Mutagenesis